Teachers’ perspectives toward bullying on physical education in elementary schools - Ipang, Setiawan; Wahyu Ragil, Kurniawan; Fatkhur , Rozi; Mugiyo, Hartono (SPORT TK-EuroAmerican Journal of Sport Sciences, 2026)
Bullying in physical education (PE) classes remains a significant issue, impacting student well-being and participation in physical activities. This study explored the perspectives of PE teachers regarding bullying in elementary school settings. Through qualitative analysis, four key themes emerged: teacher awareness of bullying, PE as a trigger for bullying, the role of learning approach models, and the impact of bullying on students. The findings indicate that while many PE teachers recognize bullying as a problem, their responses vary from proactive interventions to perceptions of bullying as normal peer interactions. Additionally, the study highlights how the competitive nature of PE can exacerbate bullying behaviors, particularly among students with lower skill levels. The selection of appropriate learning approaches, such as cooperative and inclusive teaching methods, is suggested to mitigate bullying incidents. The study further emphasizes the need for professional development programs to equip teachers with effective bullying prevention strategies. Future research should explore intervention models tailored to PE settings and conduct longitudinal studies to assess the long-term effectiveness of different teaching methodologies in reducing bullying.